A NUMERICAL SCHEME FOR SOLVING CREEPING FLOWS - Navarro, H. A.; Ferreira, V. G. (Revista de Engenharia Térmica, 2003)
This work shows an extension of the generalized Peaceman and Rachford alternating-direction implicit (ADI) scheme for simulating two-dimensional fluid flows at low Reynolds numbers. The conservation equations are solved in stream function - vorticity formulation. We compare the ADI and generalized ADI schemes, and show that the latter is more efficient to simulate a creeping flow. Numerical results demonstrating the applicability of this technique are also presented.